Pengaruh Pembelajaran Inkuiri dengan Scaffolding terhadap Keterampilan Proses Sains dan Pemahaman Konsep Siswa pada Materi Cahaya - Dimas Abdi Haidar; Lia Yuliati; Supriyono Koes Handayanto (Graduate School of Universitas Negeri Malang, 2020)
Abstract: The purpose of this study is to examine the effect of inquiry learning with scaffolding on science process skills and understanding of light material concepts in fourth grade students. This type of research is a quasi-experimental design with a non-equivalent control group. The samples taken were students of class IV A (experimental) with 25 students and class IV B (control) with 22 students. The results of this study indicate that the value of science process skills and the percentage of students' understanding of concepts in light material in the experimental class have a significant increase compared to the control class. From the results of Man-Whitney and Anacova statistics it can be concluded that, there is a significant difference in the use of Inquiry learning with scaffolding of science process skills and understanding of light material concepts in fourth grade elementary school students. Abstrak: Tujuan dari penelitian ini yaitu untuk menguji pengaruh pembelajaran Inkuiri dengan scaffolding terhadap keterampilan proses sains dan pemahaman konsep materi cahaya pada siswa kelas IV. Jenis penelitian ini merupakan eksperimen semu dengan desain non-equivalent control group. Sampel yang diambil merupakan siswa kelas IV A (eksperimen) dengan 25 siswa dan kelas IV B (kontrol) dengan 22 siswa. Hasil penelitian ini menunjukan bahwa nilai keterampilan proses sains dan persentase pemahaman konsep siswa pada materi cahaya di kelas eksperimen memiliki peningkatan signifikan dibanding kelas kontrol. Dari hasil statistik Man-Whitney dan Anacova dapat diambil kesimpulan bahwa, ada perbedaan signifikan penggunaan pembelajaran Inkuiri dengan scaffolding terhadap keterampilan proses sains dan pemahaman konsep materi cahaya pada siswa kelas IV SD.